2018
DOI: 10.1364/ol.43.000671
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable optical fiber Bragg gratings

Abstract: We demonstrate, for the first time, an inscription and wet dissolution study of Bragg gratings in a bioresorbable calcium-phosphate glass optical fiber. Bragg gratings, with average refractive index changes of 5.8×10, were inscribed using 193 nm excimer laser radiation. Results on the dissolution of the irradiated fiber in simulated physiological conditions are presented after immersing a tilted Bragg grating in a phosphate buffered saline solution for 56 h; selective chemical etching effects are also reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
(39 reference statements)
1
26
0
Order By: Relevance
“…In this sense, the possibility of inscribing FBGs in specialty fibers has provided the backbone for advanced applications in sensing and fiber lasers, particularly thanks to direct inscription. Among others, Iadicicco et al [9] reported FBGs in microstructured fibers which add refractive index sensitivity to the inherent temperature/strain sensitivity; Jovanovic et al [10] reported FBGs directly inscribed with a point-by-point technique in the inner core of a dual-core fiber, which represents the end reflectors of a fiber laser cavity; Leal-Junior et al [11] reported FBGs inscribed in a polymer fiber in the infrared, which achieves a much larger sensitivity to temperature effects, and reports also a humidity sensitivity; Pugliese et al [12] reported FBGs inscribed in a bioresorbable fiber, which has the property of being potentially absorbed by the human body after use.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the possibility of inscribing FBGs in specialty fibers has provided the backbone for advanced applications in sensing and fiber lasers, particularly thanks to direct inscription. Among others, Iadicicco et al [9] reported FBGs in microstructured fibers which add refractive index sensitivity to the inherent temperature/strain sensitivity; Jovanovic et al [10] reported FBGs directly inscribed with a point-by-point technique in the inner core of a dual-core fiber, which represents the end reflectors of a fiber laser cavity; Leal-Junior et al [11] reported FBGs inscribed in a polymer fiber in the infrared, which achieves a much larger sensitivity to temperature effects, and reports also a humidity sensitivity; Pugliese et al [12] reported FBGs inscribed in a bioresorbable fiber, which has the property of being potentially absorbed by the human body after use.…”
Section: Introductionmentioning
confidence: 99%
“…Absorption and scattering of light in tissues result from fundamental light–matter interactions and have enabled a variety of stimulation and monitoring techniques for biomedical therapy and imaging . Very recently, bioresorbable optical waveguides, photonic structures, and optical sensors working in the vis–NIR spectral region and able to operate in vivo in physiological conditions have also attracted attention for photomedicine applications ( Figure ).…”
Section: Bioresorbable Optical Devicesmentioning
confidence: 99%
“…To tackle the aforementioned criticalities, a bioresorbable optical fiber can be a promising solution , in particular if such optical fiber is able to degrade under physiological conditions in a limited and controlled amount of time. For the fiber material to be bioresorbable, it must be biocompatible, has to avoid triggering an inflammatory response and has to be eliminated from the body over time without leaving any harmful residual.…”
Section: Introductionmentioning
confidence: 99%
“…While the properties of the bioresorbable phosphate fibers have been extensively tested in a lab environment and a fiber Bragg grating sensor has been realized with them , in this article, the in vivo testing of biodegradability and toxicity of the phosphate glass optical fiber is reported for the first time. Moreover, the applicability and compatibility of such fiber is demonstrated with a fiber optic pH‐meter of own design which is based on standard multi‐mode silica fibers and was successfully used in the past for ex‐vivo pH measurement of aqueous humor during cataract surgery or for in vivo measurement of local pH in plant tissues .…”
Section: Introductionmentioning
confidence: 99%